(untitled) (Revista Ciência Agronômica, 2017)
The pollination and fertilization process directly affects the crop yield of peach. Previous studies have shown that some cultivars lack consistent cropping (yield variation) in subtropical regions. The application of boric acid at flowering can minimize this problem. This study quantified the germination of pollen grains and fruit set on 18 cultivars of peach in a subtropical region when treated with boric acid at bud. The initial spray treatments were three concentrations of boric acid (400 mgL-1, 800 mgL-1 and 1,200 mgL-1) plus a control treatment of water. Treatments were sprayed on the shoots when the flower buds were flower bud swelling on early maturing cultivars Aurora 2 and Doçura 2. There is a cultivar difference where ‘Aurora 2’ had a negative effect from the application of boric acid on the percentage of germinated pollen grains and fruit set. ‘Doçura 2’ has a positive results at the concentration of 400 mgL-1 of boric acid. In a follow-up experiment with 18 cultivars, using only the water control and 400 mgL-1 boric acid treatment, boron increases pollen grain germination and fruit set for some cultivars. The increase in germination and fruit set varies significantly among the cultivars. The concentration of 400 mgL-1 of boric acid increases pollen germination and fruit set, but not in all cultivars.